Estructura de la población del cambuto Strombus galeatus (Gastropoda: Strombidae) en Cabo Blanco, Costa Rica - Arroyo Mora, Daisy (Revista de Biología Tropical, 1998)
The conch S. galeatus used to be a common gastropod in the Pacific coast of Costa Rica. but high exploitation levels have diminished natural stocks. A natural, unexploited, population was studied in San Miguel tidal pool at Cabo Blanco Absolute Reserve. from December 1993 through December 1997. using the mark-recapture method and biometrics. This population can inmigrate and emigrate from the mostly rocky-bottom pool by its western natural en trance. From a total of 627 marked conchs. 70.3 % were adults. 23,0 % subadults and only 6.7% were juveniles, and this pattern was constant throughout the survey. Males represented 51.4% or the population. females 43.7% and undetermined individuals 4,8%. An average of 74 % of the conchs were recovered during surveys (with a mean recapture index of 14.7 %), and only 26 % of the conchs were observed. Average adult, subadult and juvenile lengths were, respectively 183.2 mm (S.D. 9.5).162.8 mm (S.D. 5,7) and 132.1 mm (5.0, 15,0). Density was estimated as 500 conch/ha.